Knowledge, attitude, and practice of personal protective equipment utilization among health care workers - Bizuayehu Atinafu Ataro; Dawit Simeon Bilate; GebreMeskel Mulatu; Temesgen Geta; Ayele Agana; Eshetu Elfios Endirias; Getachew Nigussie Bolado; Tigistu Toru; Christian Kebede; Kirubel Eshetu Haile; Mulualem Gete Feleke (Elsevier, 2024)
Background: Although healthcare personnel often face hazardous working conditions with potential exposures to a variety of toxic and infectious agents, adherence to Personal Protective Equipment (PPE) protocols is quite low. Proper utilization of PPE safeguards health care providers from hazardous working conditions and increases patients' safety. However, there is a shortage of relevant studies yet to address this gap, especially in sub-Saharan regions. Objective: The objective of the study was to determine knowledge, attitude, and practice on personal protective equipment utilization among healthcare workers. Methods: An institutional-based cross-sectional study was conducted among the participants selected using a simple random sampling technique. A logistic regression analysis was carried out to identify the associated factors. Result: The practice of PPE utilization was 78.2%. Multivariate logistic regression analysis revealed educational status, marital status, overcrowding of the working department, and supply of PPE as independent predictors of KAP of PPE utilization. Conclusion: Knowledge about PPE utilization was good; however, the practice of PPE utilization was low. Decreasing the workload of healthcare workers and improving PPE supply are demanded to boost the utilization of PPE.